Revolutionizing Basic Computer and Networking Education: An Android-Based E-Module Study at Vocational High School: Revolusi Pendidikan Dasar Komputer dan Jaringan: Kajian E-Modul Berbasis Android di Sekolah Menengah Kejuruan - Kusumayanti, Diah; Astuti, Cindy Cahyaning (Indonesian Journal of Innovation Studies, 2023)
A new subject added to the 2013 curriculum in computer engineering and networking prompted teachers to search for engaging teaching materials. This study aimed to develop an Android-based e-module for the basic computer and networking subject in the X grade of SMK Ar-Roudhoh and assess its suitability. Research and Development method using the ADDIE model was employed, with data collected through observation, questionnaires, and validation tests by media and subject matter expert teachers. An interactive Android-based e-module was developed and met the validity criteria. The media expert validator gave a score of 81.25%, and the subject matter expert validator gave a score of 80%, both in the acceptable category with revisions. The e-module is suitable as a teaching material for the basic computer and networking subject. Highlights: 1. The study aimed to develop an Android-based e-module for the basic computer and networking subject in the X grade of SMK Ar-Roudhoh and assess its suitability. 2. Research and Development method using the ADDIE model was employed, with data collected through observation, questionnaires, and validation tests by media and subject matter expert teachers. 3. The interactive Android-based e-module was developed and met the validity criteria. The e-module is suitable as a teaching material for the basic computer and networking subject.